Budaya Permintaan Maaf Di Tempat Kerja Dalam Drama Jepang: Tinjauan Sosiolinguistik - Eka Marthanty Indah Lestari (Universitas Diponegoro, 2019)
The apology is an action in which a person states his/her regret on the mistake which he/she did. The procedures in apology are closely related to the culture which is applicable in a region. This research in general aims to understand the apology culture in the workplace of Japan. The specific objectives of this research are 1) to identify the expression of apology used in the workplace; 2) to identify the apology strategy used in the workplace; and 3) to analyze the aspects which affect choices of expression and apology strategy. The qualitative research methodology was used, while the problem of research was viewed from the perspective of sociolinguistics. Source of the data in this research is a Japanese drama entitled Haken no Hinkaku (2007). In the drama, there are 78 (seventy-eight) apology expressions used in the workplace. The apology strategies are as follows: 1) directly apologizing; 2) providing explanation or stating the reason; 3) being responsible; 4) offering replacement of the damaged goods; and 5) making a promise to not repeat the same mistake. Furthermore, the aspects which play role in choosing expression and apology strategy are situation, degree of the mistake which was made, and the status of interlocutors. <a href=